Asuhan Keperawatan Pada Ny. A Dengan Post Operasi Sectio Caesarea Indikasi Riwayat Sectio Caesarea Di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Uki Sari Mustami; Tati karyawati; Siti fatimah (Lembaga Pengembangan Kinerja Dosen, 2023)
Every woman experiences the process of giving birth, it is natural for women to give birth normally, namely through the vagina or normal birth canal. If a woman cannot give birth normally, medical personnel will perform an alternative delivery to help expel the fetus. If the conditions of the mother and fetus have complications during delivery, then to immediately save both of them it is necessary to carry out delivery procedures, one of the actions taken is caesarean section delivery (Safitri, 2020).